Rapid foaming fireproof and waterproof sealant for power cable

By using fragmented fiberglass mesh and inorganic environmentally friendly flame retardant in power cable rapid foaming fire-resistant waterproof sealant, combined with electromagnetic induction heating and magnetic detonation bubble particles, the performance and cost of traditional fire-resistant sealing materials under extreme conditions is solved. High-quality problems achieve efficient and environmentally friendly fire-proof sealing effect.

CN119242260APending Publication Date: 2025-01-03衡诚能源科技(上海)有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411509919.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Traditional fire-resistant sealing materials have problems in installation, construction and environmental protection, and may not achieve the expected fire-resistant effect under extreme conditions, and the production costs are high, which limits their application.

Method used

Power cables are used to quickly foam fire-resistant and waterproof sealants, including components A and components B. Component A is doped with fragmented glass fiber webs, combined with silicone and inorganic environmentally friendly flame retardants, and heated by electromagnetic induction and Magnetic detonation bubble particles accelerate curing, improving high temperature resistance, weather resistance and chemical corrosion resistance.

Benefits of technology

It achieves excellent waterproof, anti-condensation and insulation performance, can maintain good sealing effect in complex environments, reduce production costs, extend usage time, reduce maintenance frequency, and meet environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242260A_ABST
    Figure CN119242260A_ABST
Patent Text Reader

Abstract

The invention relates to the field of electric power engineering, in particular to a fireproof material technology. The rapid foaming fireproof and waterproof sealant for the power cable comprises a component A and a component B, wherein the component A comprises a resin matrix, a foaming agent, a flame retardant, a plasticizer and a filler, and is doped with a fragmented glass fiber mesh which is used as the filler; wherein the component B comprises a cross-linking agent, a catalyst and a coupling agent. The rapid foaming fireproof and waterproof sealant for the power cable is formed by adopting an organic silicon modified polyester material, and the high temperature resistance, weather resistance and chemical corrosion resistance of the sealant are remarkably improved by introducing organic silicon on the basis of keeping the original excellent performance of polyester. And in addition, the inorganic environment-friendly flame retardant material is especially added, so that the environment-friendly requirement is met, and the safety and the environment-friendly property of the product are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electric power engineering, and in particular to fireproof material technology. Background Art

[0002] Rapid Cable Foam Fire Sealant is a material used to fill and seal holes where cables pass through walls or floors. It expands in the event of a fire to form a fire barrier that stops the spread of fire and smoke penetration. This technology plays an important role in construction and electrical engineering, especially in improving the fire safety performance of buildings.

[0003] Traditional fireproof sealing materials include asbestos, calcium silicate board, expanded perlite, etc. Although these materials have certain fireproof properties, they have some disadvantages in installation, construction and environmental protection. For example, asbestos has been proven to be harmful to human health, while materials such as calcium silicate board and expanded perlite may generate dust during construction, affecting the health of construction workers, and the expansion performance and sealing effect of these materials may not be as good as those of foaming fireproof sealants.

[0004] Compared with traditional materials, fast cable foam fireproof sealant has better expansion performance and sealing effect. It can expand rapidly in a short time to form a solid fireproof layer. However, it also has some limitations, such as adaptability to ambient temperature and humidity, long-term durability and cost issues. Under certain extreme conditions, the foam material may not achieve the expected fireproof effect, or may age and crack after long-term use, thus affecting its fireproof performance. In addition, the high production cost of fast cable foam fireproof sealant may limit its application in some cost-sensitive projects. Summary of the invention

[0005] The object of the present invention is to provide a fast-foaming fireproof and waterproof sealant for power cables to solve at least one of the above-mentioned technical problems.

[0006] The technical problem solved by the present invention can be achieved by adopting the following technical solutions:

[0007] Power cable fast foaming fireproof and waterproof sealant, including component A and component B;

[0008] The component A comprises a resin matrix, a foaming agent, a flame retardant, a plasticizer, a filler, and is doped with a fragmented glass fiber mesh, with the fragmented glass fiber mesh serving as the filler;

[0009] The B component includes a cross-linking agent, a catalyst, and a coupling agent;

[0010] In terms of weight percentage, component A contains 1.6-20% of foaming agent, 8-45% of flame retardant, 3-45% of plasticizer, 22.5-45% of filler, and the rest is resin matrix; component B contains 0.78-5.05% of catalyst, 6.5-42% of coupling agent, and the rest is cross-linking agent;

[0011] The glass fiber mesh comprises a mesh body and expanded glass fibers;

[0012] The net body is woven with warp and weft;

[0013] Both the warp and weft threads are made of fiberglass;

[0014] The lengths of at least part of the warp threads and at least part of the weft threads are beyond the mesh body to form expanded glass fibers;

[0015] The diameter of glass fiber is 6 to 10 μm;

[0016] The area of ​​the mesh is 0.6~2mm 2 , mesh area is 0.05~0.2mm 2 ;

[0017] The length of the expanded glass fiber is 0.6 to 1.8 mm;

[0018] Measured by volume, there are 3 to 5 glass fiber meshes per cubic centimeter.

[0019] In the above design, the 6-10μm glass fiber woven mesh has good softness and certain toughness. The area of ​​the mesh is 0.6-2 square millimeters, and the fragmented glass fiber mesh formed is not easy to be tangled after being mixed into the sealant as a filler. The mesh area is 0.05-0.2 square millimeters, allowing the resin matrix to pass through the mesh and the strength of the bond with the fiber mesh is stronger.

[0020] In the above design, the length of the expanded glass fiber is 0.6 to 1.8 mm. In terms of volume, there are 3 to 5 glass fiber meshes per cubic centimeter. The beneficial effect is that while ensuring that the number of glass fiber meshes per unit volume is moderate, the expanded glass fibers are encouraged to be intertwined with each other as much as possible to form a three-dimensional network structure, thereby improving the overall strength.

[0021] Furthermore, the resin matrix adopts a linear hydroxy-terminated polydimethylsiloxane with a viscosity of 500 to 3000 cps;

[0022] Azodicarbonamide is used as the foaming agent;

[0023] The flame retardant is one or more of magnesium hydroxide, aluminum hydroxide and zinc borate;

[0024] The plasticizer is one or more of dioctyl phthalate, di-n-octyl phthalate, dicyclohexyl phthalate and diisononyl phthalate;

[0025] The filler is one or more of light calcium, heavy calcium, talcum powder, kaolin, fly ash, clay, glass fiber, quartz powder and titanium dioxide.

[0026] In the above design, a polyester material modified with silicone is used to form a rapid foaming fireproof and waterproof sealant for power cables. This sealant, while maintaining the excellent properties of the original polyester, significantly improves its ability to resist high temperature, weather and chemical corrosion through the introduction of silicone. In addition, inorganic environmentally friendly flame retardant materials are specially added. This material not only has high-efficiency flame retardant properties, but also does not produce toxic and harmful gases during combustion, which meets environmental protection requirements and ensures the safety and environmental protection of the product.

[0027] Furthermore, the crosslinking agent is one of ethyl orthosilicate, tetraethoxysilane, methyltriethoxysilane, polymethyltriethoxysilane and dimethyldiethoxysilane;

[0028] The catalyst is one or more of dibutyltin dilaurate and stannous octoate;

[0029] The coupling agent used is one or more of KH330, KH550 and KH570.

[0030] Furthermore, when drawing, the glass fiber as one of the warp and weft threads passes through a space where soft magnetic powder dust floats in the air in a molten state, and is bonded with the soft magnetic powder.

[0031] When drawing, the glass fiber, which is another kind of warp and weft, passes through the space where graphite dust floats in the air in a molten state and is bonded with graphite powder;

[0032] The particle size of soft magnetic powder is between 80 and 200 nm;

[0033] The particle size of graphite powder is 6 to 10 μm.

[0034] In the above design, ferroferric oxide powder and graphite powder are bonded in the molten state of glass fiber. The beneficial effect is that the bonding is strong and uniform, the adhesive can be omitted, the bonding structure will not be damaged under high and low temperatures, the long-lasting bonding strength between the glass fiber and the silicone base material is guaranteed, and the glass fiber can withstand high-temperature electromagnetic induction heating.

[0035] As one of the warp or weft, the glass fiber is bonded with soft magnetic powder, and the soft magnetic powder has soft magnetic properties.

[0036] The invention is also equipped with a device having an oscillating circuit connected to an electromagnet. The electromagnet is close to the sealant to generate a magnetic field with periodic direction changes. The glass fiber bonded with soft magnetic powder drives the glass fiber mesh to vibrate as a whole under the action of the magnetic field with periodic direction changes. The beneficial effects are: firstly, the vibration of the glass fiber mesh can play a stirring role, so that the components of the rapid foaming fireproof and waterproof sealant for power cables are better mixed; secondly, the vibration of the glass fiber mesh can make the contact between the fiber mesh and the rapid foaming fireproof and waterproof sealant for power cables more firm, thereby eliminating surface tension.

[0037] As the other one of the warp or weft, the glass fiber is bonded with graphite powder, and the graphite powder in the fluid glue makes the fluid glue have a certain conductivity.

[0038] It is also equipped with an electromagnetic induction heating device, which is set near the fluid glue. The electromagnetic induction heating device can emit a high-frequency magnetic field. The glass fiber is bonded with soft magnetic powder, which has soft magnetic properties. The magnetic field can be introduced into the depth of the fluid glue to form a relatively uniform magnetic field distributed in the fluid glue, thereby making the conductive fluid glue relatively uniformly heated, thereby increasing the ambient temperature during curing. Its beneficial effect is that the heating temperature of the fluid glue can be controlled by changing the frequency and amplitude of the magnetic field through the electromagnetic induction heating device, thereby controlling the efficiency and speed of curing.

[0039] Furthermore, it also includes bubble particles doped with magnetically detonated bubble particles as fillers;

[0040] The bubble particle has an airtight membrane filled with air at 1.2 to 1.35 atmospheric pressures and with an air humidity of 80 to 90%; and also includes a magnetic needle;

[0041] The magnetic needle includes a needle tip and a needle body, wherein the needle tip is made of a soft magnetic material and the needle body is made of a non-magnetic material;

[0042] The volume of bubble particles is 2.5~3.5mm 3 ;

[0043] There are 2 to 4 bubble particles per cubic centimeter.

[0044] For further optimization, the membrane of the bubble particles is made of polyethylene; the needle tip is made of iron-silicon alloy, and the needle body is made of PE plastic.

[0045] In the above design, in order to further increase the curing speed of the sealant, bubble particles are added to the sealant, the bubble particles are filled with moist air with a humidity of 80-90%, and magnetic needles for detonating the bubble particles are also arranged in the bubble particles.

[0046] The invention is also equipped with a device, including an oscillating circuit connected to an electromagnet to generate a magnetic field with periodic direction changes. The electromagnet is close to the colloid, and under the action of the magnetic field provided by the equipment, the needle tip of the magnetic needle is guided to puncture the bubble particles made of polyethylene film. The polyethylene is elastic and will burst after being punctured by the needle tip, thereby releasing the humid air in the bubble particles inside the sealant. The beneficial effect is that the water molecules contained in the released air react chemically with the cross-linking agent inside the rapid foaming fireproof and waterproof sealant of the power cable to form a three-dimensional cross-linking network, thereby accelerating the curing efficiency and speed of the sealant.

[0047] Furthermore, the preparation method of component A comprises the following steps:

[0048] Step S1, activation: placing the filler in a reactor for activation treatment to improve the compatibility and bonding strength between the filler and the base material; after the activation treatment is completed, the reactor is sealed and left to stand for 6 to 12 hours so that the filler can fully absorb the activator and reach the best reaction state;

[0049] Step S2, base material mixing: various base materials are added into another reaction kettle according to the formula ratio, the base materials including resin matrix, foaming agent and plasticizer. After the addition is completed, the reaction kettle is closed, and the vacuum device is started to evacuate the reaction kettle until the air pressure in the kettle is lower than 130 Bar, and then the stirring device is started to fully stir the various base materials to ensure the uniformity and stability of the mixture;

[0050] Step S3, adding flame retardant: continue to add flame retardant into the reaction kettle, seal and evacuate until the pressure is lower than 130 Bar, and continue to stir until it is completely uniform;

[0051] Step S4, dispersion treatment: add the activated and stationary filler into the reactor, seal it again and evacuate it to a pressure lower than 130 Bar, and continue stirring and dispersing for 4 hours;

[0052] Step S5, testing and packaging: various performance tests are performed on the mixture to ensure that it meets the quality standards. The products that pass the tests enter the filling process, and the mixture is filled into corresponding containers for packaging to obtain the finished product of component A.

[0053] Furthermore, the preparation method of component B comprises the following steps:

[0054] Step S1, mixing raw materials: adding a cross-linking agent, a catalyst and a coupling agent into a reaction kettle according to the formula ratio, closing the reaction kettle after the addition is completed, starting a vacuum device to draw a vacuum until the pressure in the kettle is lower than 130 Bar, starting a stirring device, stirring for 15 to 30 minutes, and fully stirring various raw materials to ensure the uniformity of the mixture;

[0055] Step S2, standing: keep the reaction kettle sealed and in a vacuum state, and stand for 1 to 2 hours to ensure the stability of the mixture;

[0056] Step S3, testing and packaging: various performance tests are performed on the mixture to ensure that it meets the quality standards. The products that pass the tests enter the filling process, and the mixture is filled into corresponding containers for packaging to obtain the finished product of component B.

[0057] In the above design, the production cost of preparing the fast-foaming fireproof and waterproof sealant for power cables is reduced by stirring the mixture and dispersing under vacuum conditions in the reactor, thereby achieving the purpose of mass production.

[0058] The beneficial effect of the present invention is that the sealant has excellent waterproof and anti-condensation properties and can maintain a good sealing effect in various complex environments.

[0059] Its beneficial effect is also that it has excellent insulation performance and can effectively prevent short circuit and leakage caused by moisture.

[0060] In addition, the sealant also has good anti-small animal function, which can effectively prevent the invasion of small animals, such as mice, etc. Due to its foaming characteristics, the sealant can easily fill cable holes of various shapes and sizes during use, and has good adaptability and easy expansion. At the same time, the sealant has a beautiful appearance design, which can be integrated with the surrounding environment and enhance the overall visual effect.

[0061] Its beneficial effect is also that the sealant has a long effective use time and can maintain its excellent performance over a long period of time, thereby reducing the frequency of maintenance and replacement and lowering long-term operating costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0063] Figure 1 is a schematic diagram of a fiberglass mesh in fragmented form;

[0064] Figure 2 This is a schematic diagram of the structure of the network

[0065] Figure 3 It is a schematic diagram of the structure of bubble particles.

[0066] Explanation of symbols:

[0067] 1. mesh; 2. expanded glass fiber; 3. bubble particles; 11. warp; 12. weft; 30. film; 31. magnetic needle. DETAILED DESCRIPTION

[0068] In order to make the above-mentioned objects, features and advantages of the present invention more clearly understood, the specific implementation modes of the present invention are described in detail below in conjunction with the accompanying drawings.

[0069] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0070] Secondly, the present invention is described in detail with reference to schematic diagrams. When describing the embodiments of the present invention in detail, for the sake of convenience, the cross-sectional diagrams showing the device structure will not be partially enlarged according to the general scale, and the schematic diagrams are only examples, which should not limit the scope of protection of the present invention. In addition, in actual production, the three-dimensional dimensions of length, width and depth should be included.

[0071] Furthermore, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.

[0072] Power cable fast foaming fireproof and waterproof sealant, including component A and component B;

[0073] The component A comprises a resin matrix, a foaming agent, a flame retardant, a plasticizer, a filler, and is doped with a fragmented glass fiber mesh, with the fragmented glass fiber mesh serving as the filler;

[0074] The B component includes a cross-linking agent, a catalyst, and a coupling agent;

[0075] In terms of weight percentage, component A contains 1.6-20% of foaming agent, 8-45% of flame retardant, 3-45% of plasticizer, 22.5-45% of filler, and the rest is resin matrix; component B contains 0.78-5.05% of catalyst, 6.5-42% of coupling agent, and the rest is cross-linking agent;

[0076] The glass fiber mesh includes a mesh body 1 and expanded glass fibers 2;

[0077] The net body 1 is woven by warp threads 11 and weft threads 12;

[0078] The warp threads 11 and the weft threads 12 are both made of glass fibers;

[0079] The lengths of at least part of the warp threads 11 and at least part of the weft threads 12 exceed the mesh body 1 to form extended glass fibers 2;

[0080] The diameter of glass fiber is 6 to 10 μm;

[0081] The area of ​​the mesh 1 is 0.6 to 2 mm 2 , mesh area is 0.05~0.2mm 2 ;

[0082] The length of the extended glass fiber 2 is 0.6 to 1.8 mm;

[0083] Measured by volume, there are 3 to 5 glass fiber meshes per cubic centimeter.

[0084] In this embodiment, the mesh woven from 6-10 μm glass fibers has good softness and certain toughness. The area of ​​the mesh body 1 is 0.6-2 square millimeters, and the fragmented glass fiber mesh formed is not easy to be tangled after being mixed into the sealant as a filler. The mesh area is 0.05-0.2 square millimeters, allowing the resin matrix to pass through the mesh and the strength of the combination with the fiber mesh is stronger.

[0085] In this embodiment, the length of the extended glass fiber 2 is 0.6 to 1.8 mm. In terms of volume, there are 3 to 5 glass fiber meshes per cubic centimeter. The beneficial effect is that while ensuring that the number of glass fiber meshes per unit volume is moderate, the extended glass fibers 2 are encouraged to be intertwined with each other as much as possible to form a three-dimensional network structure, thereby improving the overall strength.

[0086] Furthermore, the resin matrix adopts a linear hydroxy-terminated polydimethylsiloxane with a viscosity of 500 to 3000 cps;

[0087] Azodicarbonamide is used as the foaming agent;

[0088] The flame retardant is one or more of magnesium hydroxide, aluminum hydroxide and zinc borate;

[0089] The plasticizer is one or more of dioctyl phthalate, di-n-octyl phthalate, dicyclohexyl phthalate and diisononyl phthalate;

[0090] The filler is one or more of light calcium, heavy calcium, talcum powder, kaolin, fly ash, clay, glass fiber, quartz powder and titanium dioxide.

[0091] In this embodiment, a polyester material modified with silicone is used to form a rapid foaming fireproof and waterproof sealant for power cables. This sealant, while maintaining the excellent properties of the original polyester, significantly improves its high temperature resistance, weather resistance and chemical corrosion resistance through the introduction of silicone. In addition, an inorganic environmentally friendly flame retardant material is specially added. This material not only has efficient flame retardant properties, but also does not produce toxic and harmful gases during combustion, meets environmental protection requirements, and ensures the safety and environmental protection of the product.

[0092] Furthermore, the crosslinking agent is one of ethyl orthosilicate, tetraethoxysilane, methyltriethoxysilane, polymethyltriethoxysilane and dimethyldiethoxysilane;

[0093] The catalyst is one or more of dibutyltin dilaurate and stannous octoate;

[0094] The coupling agent used is one or more of KH330, KH550 and KH570.

[0095] Furthermore, when drawing, the glass fiber as one of the warp 11 and the weft 12 passes through the space where the soft magnetic powder dust floats in the air in a molten state, and is bonded with the soft magnetic powder;

[0096] When drawing, the glass fiber, which is another one of the warp 11 and the weft 12, passes through a space where graphite dust floats in the air in a molten state, and is bonded with graphite powder;

[0097] The particle size of soft magnetic powder is between 80 and 200 nm;

[0098] The particle size of graphite powder is 6 to 10 μm.

[0099] In this embodiment, ferroferric oxide powder and graphite powder are bonded in the molten state of glass fiber. The beneficial effect is that the bonding is strong and uniform, the adhesive can be omitted, the bonding structure will not be damaged under high and low temperatures, the long-lasting bonding strength between the glass fiber and the silicone base material is ensured, and the glass fiber can withstand high-temperature electromagnetic induction heating.

[0100] As one of the warp threads 11 or the weft threads 12, the glass fiber thereof is bonded with soft magnetic powder, and the soft magnetic powder has soft magnetic properties.

[0101] The invention is also equipped with a device having an oscillating circuit connected to an electromagnet. The electromagnet is close to the sealant to generate a magnetic field with periodic direction changes. The glass fiber bonded with soft magnetic powder drives the glass fiber mesh to vibrate as a whole under the action of the magnetic field with periodic direction changes. The beneficial effects are: firstly, the vibration of the glass fiber mesh can play a stirring role, so that the components of the rapid foaming fireproof and waterproof sealant for power cables are better mixed; secondly, the vibration of the glass fiber mesh can make the contact between the fiber mesh and the rapid foaming fireproof and waterproof sealant for power cables more firm, thereby eliminating surface tension.

[0102] As the other one of the warp threads 11 or the weft threads 12, the glass fiber thereof is bonded with graphite powder, and the graphite powder in the fluid glue makes the fluid glue have a certain conductivity.

[0103] It is also equipped with an electromagnetic induction heating device, which is set near the fluid glue. The electromagnetic induction heating device can emit a high-frequency magnetic field. The glass fiber is bonded with soft magnetic powder, which has soft magnetic properties. The magnetic field can be introduced into the depth of the fluid glue to form a relatively uniform magnetic field distributed in the fluid glue, thereby making the conductive fluid glue relatively uniformly heated, thereby increasing the ambient temperature during curing. Its beneficial effect is that the heating temperature of the fluid glue can be controlled by changing the frequency and amplitude of the magnetic field through the electromagnetic induction heating device, thereby controlling the efficiency and speed of curing.

[0104] Furthermore, it also includes bubble particles 3 doped with the bubble particles 3 detonated by magnetic force, with the bubble particles 3 as filler;

[0105] The bubble particle 3 has an airtight membrane 30, the membrane 30 is filled with air at 1.2 to 1.35 atmospheres, and the air humidity is 80 to 90%; and also includes a magnetic needle 31;

[0106] The magnetic needle 31 includes a needle tip and a needle body, wherein the needle tip is made of a soft magnetic material and the needle body is made of a non-magnetic material;

[0107] The volume of the bubble particles 3 is between 2.5 and 3.5 mm 3 ;

[0108] There are 2 to 4 bubble particles per cubic centimeter3.

[0109] For further optimization, the membrane 30 of the bubble particle 3 is made of polyethylene; the needle tip is made of iron silicon alloy, and the needle body is made of PE plastic.

[0110] In this embodiment, in order to further increase the curing speed of the sealant, bubble particles 3 are added to the sealant. The bubble particles 3 are filled with humid air with a humidity of 80-90%. Magnetic needles 31 for detonating the bubble particles 3 are also provided in the bubble particles 3.

[0111] A device is also equipped, including an oscillating circuit connected to an electromagnet to generate a magnetic field with periodic direction changes. The electromagnet is close to the colloid, and under the action of the magnetic field provided by the equipped device, the needle tip of the magnetic needle 31 is guided to puncture the bubble particles 3 made of polyethylene film 30. The polyethylene has elasticity and will burst after being punctured by the needle tip, thereby releasing the humid air in the bubble particles 3 inside the sealant. The beneficial effect is that the water molecules contained in the released air react chemically with the cross-linking agent inside the fast-foaming fire-proof and waterproof sealant for power cables to form a three-dimensional cross-linking network, thereby accelerating the curing efficiency and speed of the sealant.

[0112] Embodiment 1:

[0113] Component A: 100 parts of linear hydroxy-terminated polydimethylsiloxane (1000 cps), 10 parts of azodicarbonamide, 50 parts of magnesium hydroxide, 20 parts of plasticizer, and 30 parts of filler.

[0114] Component B: 40 parts of tetraethyl orthosilicate, 1 part of dibutyltin dilaurate, and 5 parts of coupling agent.

[0115] Mixing and foaming: Mix components A and B in a ratio of 10:1, inject into the cable holes, and foam and solidify at room temperature. The volume expands by about 9 times and the temperature rises by about 45K.

[0116] Performance test: hydrophobic angle>110°, Shore hardness after curing 60A.

[0117] Embodiment 2:

[0118] Component A: 120 parts of linear hydroxy-terminated polydimethylsiloxane (1500 cps), 15 parts of azodicarbonamide, 60 parts of aluminum hydroxide, 25 parts of plasticizer, and 40 parts of filler.

[0119] Component B: 50 parts of tetraethoxysilane, 0.8 parts of stannous octoate, and 10 parts of another type of coupling agent.

[0120] Mixing and foaming: Mix components A and B in a ratio of 8:1, inject into the cable holes, and foam and solidify at room temperature. The volume expands by about 11 times and the temperature rises by about 50K.

[0121] Performance test: hydrophobic angle>115°, Shore hardness after curing 65A.

[0122] Embodiment 3:

[0123] Component A: 150 parts of linear hydroxy-terminated polydimethylsiloxane (2000cps), 20 parts of azodicarbonamide, a mixture of magnesium hydroxide and aluminum hydroxide (30 parts each), 30 parts of plasticizer, and 50 parts of special filler.

[0124] Component B: 30 parts of methyltriethoxysilane, 1.2 parts of dibutyltin dilaurate, and 8 parts of a new coupling agent.

[0125] Mixing and foaming: Mix components A and B in a ratio of 7:1, inject into the cable holes, and foam and solidify under slight heating conditions. The volume expands by about 13 times and the temperature rises by about 55K.

[0126] Performance test: hydrophobic angle>120°, Shore hardness after curing 70A.

[0127] Embodiment 4:

[0128] Component A: 180 parts of linear terminal hydroxyl polydimethylsiloxane (2500cps), 25 parts of high-efficiency foaming agent, a specially treated flame retardant mixture (20 parts each of magnesium hydroxide, aluminum hydroxide, and zinc borate), 35 parts of plasticizer, and 60 parts of nano-scale filler.

[0129] Component B: 40 parts of polymethyltriethoxysilane, mixed catalyst (0.5 parts each of dibutyltin dilaurate and stannous octoate), and 12 parts of multifunctional coupling agent.

[0130] Mixing and foaming: Mix components A and B in a ratio of 6:1, inject into the cable holes, and foam and solidify at a controlled temperature. The volume expands by about 14 times and the temperature rises by about 58K.

[0131] Performance test: hydrophobic angle>125°, Shore hardness after curing 75A.

[0132] Embodiment 5:

[0133] Component A: 200 parts of linear terminal hydroxyl polydimethylsiloxane (3000cps), 30 parts of high-performance foaming agent, optimized flame retardant combination (40 parts of magnesium hydroxide, 30 parts of zinc borate), 40 parts of advanced plasticizer, and 70 parts of high-strength filler.

[0134] Component B: 50 parts of dimethyldiethoxysilane, 1.5 parts of high-efficiency catalyst (mainly dibutyltin dilaurate), and 15 parts of special coupling agent.

[0135] Mixing and foaming: Precisely control the mixing ratio of components A and B (5:1), inject into the cable holes by high-pressure injection, and foam and solidify under precisely controlled temperature and pressure. The volume expansion is up to 15 times, and the temperature rise is precisely controlled within 60K.

[0136] Performance test: The hydrophobic angle is extremely high, almost reaching a super-hydrophobic state. After curing, the Shore hardness exceeds 80A, showing extremely high overall hardness.

[0137] Reactive example:

[0138] Taking tetraethyl orthosilicate as a crosslinking agent as an example, it undergoes a condensation reaction with the resin matrix under the action of a catalyst to form a three-dimensional network structure. At the same time, the foaming agent decomposes to produce gas, causing the sealant to expand rapidly. The simplified reaction formula is as follows:

[0139]

[0140]

[0141] Comparison of Examples:

[0142] Example Volume increase ratio Temperature rise control(K) Hydrophobic angle (°) Hardness after curing (Shore A) 1 9 45 112 60 2 11 50 115 65 3 13 55 118 70 4 14 58 120 75 5 15 60 122 80

[0143] It can be seen from the comparison of the above embodiments that with the adjustment of the amount of foaming agent and the activity of the catalyst, the volume expansion ratio, temperature rise control, hydrophobicity and hardness after curing of the sealant are optimized.

[0144] Furthermore, in order to provide a concise description of exemplary embodiments, all features of an actual embodiment may not be described, i.e., those features that are not relevant to the best mode presently contemplated for carrying out the invention or those features that are not relevant to implementing the invention.

[0145] It should be understood that in the development of any actual implementation, as in any engineering or design project, numerous implementation-specific decisions may be made. Such a development effort may be complex and time-consuming, but for those of ordinary skill having the benefit of this disclosure, the development effort will be a routine task of design, fabrication, and production without undue experimentation.

[0146] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. Rapid foaming fireproof and waterproof sealant for power cables, characterized by: It includes component A and component B; The component A comprises a resin matrix, a foaming agent, a flame retardant, a plasticizer, a filler, and is doped with a fragmented glass fiber mesh, with the fragmented glass fiber mesh serving as the filler; The B component includes a cross-linking agent, a catalyst, and a coupling agent; In terms of weight percentage, component A contains 1.6-20% of foaming agent, 8-45% of flame retardant, 3-45% of plasticizer, 22.5-45% of filler, and the rest is resin matrix; component B contains 0.78-5.05% of catalyst, 6.5-42% of coupling agent, and the rest is cross-linking agent; The glass fiber mesh comprises a mesh body and expanded glass fibers; The net body is woven with warp and weft; Both the warp and weft threads are made of fiberglass; The lengths of at least part of the warp threads and at least part of the weft threads are beyond the mesh body to form expanded glass fibers; The diameter of glass fiber is 6 to 10 μm; The area of ​​the mesh is 0.6~2mm 2 , mesh area is 0.05~0.2mm 2 ; The length of the expanded glass fiber is 0.6 to 1.8 mm; Measured by volume, there are 3 to 5 glass fiber meshes per cubic centimeter.

2. The rapid foaming fireproof and waterproof sealant for power cables according to claim 1, characterized in that: The resin matrix adopts a linear hydroxy-terminated polydimethylsiloxane with a viscosity of 500 to 3000 cps; Azodicarbonamide is used as the foaming agent; The flame retardant is one or more of magnesium hydroxide, aluminum hydroxide and zinc borate; The plasticizer is one or more of dioctyl phthalate, di-n-octyl phthalate, dicyclohexyl phthalate and diisononyl phthalate; The filler is one or more of light calcium, heavy calcium, talcum powder, kaolin, fly ash, clay, glass fiber, quartz powder and titanium dioxide.

3. The rapid foaming fireproof and waterproof sealant for power cables according to claim 1, characterized in that: The crosslinking agent is one of ethyl orthosilicate, tetraethoxysilane, methyltriethoxysilane, polymethyltriethoxysilane and dimethyldiethoxysilane; The catalyst is one or more of dibutyltin dilaurate and stannous octoate; The coupling agent used is one or more of KH330, KH550 and KH570.

4. The rapid foaming fireproof and waterproof sealant for power cables according to claim 1, characterized in that: When drawing, the glass fiber, which is one of the warp and weft threads, passes through the space where soft magnetic powder dust floats in the air in a molten state, and is bonded with soft magnetic powder. When drawing, the glass fiber, which is another kind of warp and weft, passes through the space where graphite dust floats in the air in a molten state and is bonded with graphite powder; The particle size of soft magnetic powder is between 80 and 200 nm; The particle size of graphite powder is 6 to 10 μm.

5. The rapid foaming fireproof and waterproof sealant for power cables according to claim 1, characterized in that: It also includes bubble particles doped with gas bubble particles detonated by magnetic force, using the bubble particles as fillers; The bubble particles have an airtight membrane filled with air at 1.2 to 1.35 atmospheres and a humidity of 80 to 90%. Also includes a magnetic needle; The magnetic needle includes a needle tip and a needle body, wherein the needle tip is made of a soft magnetic material and the needle body is made of a non-magnetic material; The volume of bubble particles is 2.5~3.5mm 3 ; There are 2 to 4 bubble particles per cubic centimeter.

6. The rapid foaming fireproof and waterproof sealant for power cables according to claim 5, characterized in that: The membrane of the bubble particles is made of polyethylene; The needle tip is made of iron silicon alloy and the needle body is made of PE plastic.

7. The rapid foaming fireproof and waterproof sealant for power cables according to claim 1, characterized in that: The preparation method of component A comprises the following steps: Step S1, activation: placing the filler in a reactor for activation treatment to improve the compatibility and bonding strength between the filler and the base material; after the activation treatment is completed, the reactor is sealed and left to stand for 6 to 12 hours so that the filler can fully absorb the activator and reach the best reaction state; Step S2, base material mixing: various base materials are added into another reaction kettle according to the formula ratio, the base materials including resin matrix, foaming agent and plasticizer. After the addition is completed, the reaction kettle is closed, and the vacuum device is started to evacuate the reaction kettle until the air pressure in the kettle is lower than 130 Bar, and then the stirring device is started to fully stir the various base materials to ensure the uniformity and stability of the mixture; Step S3, adding flame retardant: continue to add flame retardant into the reaction kettle, seal and evacuate until the pressure is lower than 130 Bar, and continue to stir until it is completely uniform; Step S4, dispersion treatment: add the activated and stationary filler into the reactor, seal it again and evacuate it to a pressure lower than 130 Bar, and continue stirring and dispersing for 4 hours; Step S5, testing and packaging: various performance tests are performed on the mixture to ensure that it meets the quality standards. The products that pass the tests enter the filling process, and the mixture is filled into corresponding containers for packaging to obtain the finished product of component A.

8. The rapid foaming fireproof and waterproof sealant for power cables according to claim 1, characterized in that: The preparation method of component B comprises the following steps: Step S1, mixing raw materials: adding a cross-linking agent, a catalyst and a coupling agent into a reaction kettle according to the formula ratio, closing the reaction kettle after the addition is completed, starting a vacuum device to draw a vacuum until the pressure in the kettle is lower than 130 Bar, starting a stirring device, stirring for 15 to 30 minutes, and fully stirring various raw materials to ensure the uniformity of the mixture; Step S2, standing: keep the reaction kettle sealed and in a vacuum state, and stand for 1 to 2 hours to ensure the stability of the mixture; Step S3, testing and packaging: various performance tests are performed on the mixture to ensure that it meets the quality standards. The products that pass the tests enter the filling process, and the mixture is filled into corresponding containers for packaging to obtain the finished product of component B.

Citation Information

Cited By

  • Curing adhesive adjusting and implementing process for electric power construction site

    CN119286470A

  • Implementation Process for Adjusting Curing Adhesive at Electric Power Construction Site

    CN119286470B